Pengaruh Current Ratio, Net Profit Margin dan Modal Terhadap Nilai Perusahaan - Rita Nengsih (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
This study aims to examine the effect of Current Ratio (CR), Net Profit Margin (NPM) and capital on firm value in manufacturing companies listed on the Indonesia Stock Exchange for the period 2012 - 2017 simultaneously and partially. Sampling was done by purposive sampling technique. Based on predetermined criteria obtained a sample of 11 companies. The results of the research showed that the Current Ratio, Net Profit Margin and capital simultaneous and partial effect on the value of the company in manufacturing companies listed on the Indonesia Stock Exchange for the period 2012-2017. Correlation coefficient (R) of 0.650 which shows that the degree of relationship between the independent variable with the dependent variable of 0.650 or 65%. The coefficient of determination (R2) is 0.403, meaning that any changes in the company's value variable can be explained by changes in the Current Ratio, Net Profit Margin and capital variables of 0.403 or 40.3%. While the remaining 59.7% is explained by other variables outside of this study.